Magic and Collage: Language in Ginsberg’s "Wichita Vortex Sutra" - Elisa Sabbadin (Ideas: Journal of English Literary Studies)
"Wichita Vortex Sutra" might be Allen Ginsberg’s most successful anti-war poem. Written in the technique of the collage, and inspired by Burroughs' cut-ups, the poem presents a variety of voices. These include a Whitmanian, prophetic tone which becomes increasingly prevalent and the mediatic chaos of the news, featuring advertising, newspaper extracts, and radio broadcasts. In "Wichita Vortex Sutra," Ginsberg’s use of language is especially noteworthy: on the one hand, the poet charges language with a spiritual, magical power, and on the other hand, he destroys it, fragments it, and recreates it through the collage. This article explores Ginsberg’s experiments ‘with’ and ‘beyond’ language in this poem, analysing his use of voice throughout the piece and his philosophy of the cut-up. Ultimately, this article proposes an understanding of "Wichita Vortex Sutra" as a ‘magical collage,’ as a place where the spiritual and the political, the personal and the public, peacefulness and violence, and the East and the West meet.